Boost converter with adaptive reference tracking control for dimmable white LED drivers. Issue 6 (June 2015) - Liu, Pang-Jung; Hsu, Yi-Chieh
Abstract An LED driver consisting of dimmable current regulators and a boost converter with adaptive reference tracking control (ARTC) is proposed. The ARTC is realized with only one integrator and one subtractor to detect the voltage variation among the current regulators and then to generate an adaptive reference tracking voltage. Based on the reference tracking voltage, the driving voltage of the boost converter is dynamically adjusted, so as to not only maintain a minimum voltage on the current regulator but also keep the required LED-string current. A prototype control circuit including ARTC and PWM control fabricated with TSMC 0.35-μm 2P4M CMOS process validates the proposed technique. The measurement results show that the driving voltage of the boost converter is automatically regulated to compensate for the voltage alteration on the current regulators. Furthermore, the overall efficiency of the LED driver with ARTC is 6.1% better than that of the LED driver without ARTC.